PERAN PEMERINTAH DALAM PEMBERDAYAAN MASYARAKAT DI KAWASAN BANDARA INTERNASIONAL JAWA BARAT - Rizky Ilhami (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Pasundan Bandung, 2019)
Abstract The West Java Provincial Government has set out to develop the West Java International Airport (BIJB) in Kertajati Subdistrict, Majalengka Regency and to become the spatial layout of the surrounding area integrated into an airport city (aeorocity). This study discusses the development of an airport city or aerotropolis based on the literature study research method (meta analysis) which is then associated with the Kertajati spatial concept. In community empowerment (people empowerment) to increase the ability to choose and open opportunities to choose meaningful means is to increase the ability to make decisions and open opportunities to participate in decision making. The community empowerment strategy, in the Majalengka District Medium-Term Development Plan (RPJMD), has made several efforts to develop the regions and communities in the BIJB region by making policies or regulations that are in line with plans and policies related to BIJB development and Kertajati Aerocity, the RTRW and RDTR which is still a legal process.